GREENING THE SCIENCE CLASSROOM: A COMPREHENSIVE REVIEW ENVIRONMENTAL EDUCATION PRACTICES - Juwita Lestari; Maslinawati Mohamed; M. Harja Efendi; Nining Purwati (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
The implementation of a high-quality education system is necessary to face all the rapid changes in the world. The education system needs to be adapted to the problems faced such as environmental problems faced by modern humans today. Green education is an education system consisting of programs, tools and policies that aim to produce environmentally sustainable individuals. Eco-friendly education and training that emphasizes the sustainable use of resources and the application of environmental conservation is the idea behind greening the classroom. This systematic review aims to review the development and implementation of environmental education for greening science classrooms. The systematic review was designed based on the PRISMA Statement (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). The review was conducted using the three steps listed in the PRISMA diagram, including identification, screening and inclusion. Furthermore, data sources came from SCOPUS, Google Scholar and ERIC, articles from third sites were only retrieved between 2018 and 2024. Several criteria for evaluation and scoring were considered. The article search was refocused by using keywords related to the topic and question statement. Further review of the articles resulted in three major themes. These themes consisted of greening science classrooms and environmental education, challenges or barriers in implementing environmental education and also innovative pedagogical strategies. It is hoped that this study will serve as a reference in the development of environmental education and future researchers.